FBH1 helicase disrupts RAD51 filaments in vitro and modulates homologous recombination in mammalian cells - Simandlova, Jitka; Zagelbaum, Jennifer; Payne, Miranda J; Chu, Wai Kit; Shevelev, Igor; Hanada, Katsuhiro; Chatterjee, Sujoy; Reid, Dylan A; Liu, Ying; Janscak, Pavel; Rothenberg, Eli; Hickson, Ian D (The Journal of biological chemistry, 2013)
Efficient repair of DNA double strand breaks and interstrand cross-links requires the homologous recombination (HR) pathway, a potentially error-free process that utilizes a homologous sequence as a repair template. A key player in HR is RAD51, the eukaryotic ortholog of bacterial RecA protein. RAD51 can polymerize on DNA to form a nucleoprotein filament that facilitates both the search for the homologous DNA sequences and the subsequent DNA strand invasion required to initiate HR. Because of its pivotal role in HR, RAD51 is subject to numerous positive and negative regulatory influences. Using a combination of molecular genetic, biochemical, and single-molecule biophysical techniques, we provide mechanistic insight into the mode of action of the FBH1 helicase as a regulator of RAD51-dependent HR in mammalian cells. We show that FBH1 binds directly to RAD51 and is able to disrupt RAD51 filaments on DNA through its ssDNA translocase function. Consistent with this, a mutant mouse embryonic stem cell line with a deletion in the FBH1 helicase domain fails to limit RAD51 chromatin association and shows hyper-recombination. Our data are consistent with FBH1 restraining RAD51 DNA binding under unperturbed growth conditions to prevent unwanted or unscheduled DNA recombination.
Keywords: Protein Binding; DNA Recombination; DNA Damage; F-Box Proteins; Homologous Recombination; DNA vazebné proteiny; Rad51 Recombinase; homologní rekombinace; rekombinasa Rad51; Multienzyme Complexes; chromatin; DNA Helicase; Embryonic Stem Cells; embryonální kmenové buňky; DNA Repair; Chromatin; kultivované buňky; vazba proteinů; F-box proteiny; Animals; lidé; DNA Helicases; DNA-helikasy; Humans; zvířata; myši; DNA; multienzymové komplexy; DNA Replication; Cells, Cultured; Mice; DNA-Binding Proteins